2021
DOI: 10.1016/j.jcmgh.2021.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Exocrine Pancreas and Associated Diseases

Abstract: Differences in pancreatic anatomy, size, and function exist in men and women. The anatomical differences could contribute to the increase in complications associated with pancreatic surgery in women. Although diagnostic criteria for pancreatitis are the same in men and women, major sex differences in etiology are reported. Alcohol and tobacco predominate in men, whereas idiopathic and obstructive etiologies predominate in women. Circulating levels of estrogens, progesterone, and androgens contribute significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 142 publications
0
10
0
Order By: Relevance
“…As expected, the vast majority of these differences occurred at sites located on the X chromosome (n = 12,242 (94.5%), mean male-female difference = 0.18 (SD = 0.12), range of male-female differences = 0.69 – 0.01), although a notable proportion were autosomal (n = 646 (4.99%), mean male-female difference = 0.048 (SD = 0.037), range of male-female differences = 0.30 – 0.009) ( Supplementary Table 11 ). This may indicate sex-specific differences in gene regulation in the developing pancreas and is an interesting observation given evidence for male-female differences in pancreatic size and function (Wang et al, 2021, Yong et al, 2022). The top-ranked autosomal DMP between males and females was cg06513015 (difference in mean DNA methylation = 0.27, P = 2.34 × 10 −78 ) which is annotated to the promoter regions of the ERV3-1 gene; of note this site has previously been shown to have significantly higher DNA methylation in newborn females compared to males (Hu et al, 2023, Santos et al, 2023) ( Supplementary Figure 6 ).…”
Section: Resultsmentioning
confidence: 81%
“…As expected, the vast majority of these differences occurred at sites located on the X chromosome (n = 12,242 (94.5%), mean male-female difference = 0.18 (SD = 0.12), range of male-female differences = 0.69 – 0.01), although a notable proportion were autosomal (n = 646 (4.99%), mean male-female difference = 0.048 (SD = 0.037), range of male-female differences = 0.30 – 0.009) ( Supplementary Table 11 ). This may indicate sex-specific differences in gene regulation in the developing pancreas and is an interesting observation given evidence for male-female differences in pancreatic size and function (Wang et al, 2021, Yong et al, 2022). The top-ranked autosomal DMP between males and females was cg06513015 (difference in mean DNA methylation = 0.27, P = 2.34 × 10 −78 ) which is annotated to the promoter regions of the ERV3-1 gene; of note this site has previously been shown to have significantly higher DNA methylation in newborn females compared to males (Hu et al, 2023, Santos et al, 2023) ( Supplementary Figure 6 ).…”
Section: Resultsmentioning
confidence: 81%
“…It is reported that Cae is a cholecystokininpancreozymin analog and is used to successfully cause AP in male mice, which belongs to a hormone-induced model (54). In addition, the effects of estrogens in female mice in the setting of AP are complex and vary with sex (55). To avoid the influence of estrogens in female mice, male mice are favorably used to establish the AP model compared with the female ones (56).…”
Section: Discussionmentioning
confidence: 99%
“…The relatively higher incidence rates of PC in males have been shown in certain regions, for example, in 2020 in Eastern and Western Europe (with an age-standardized incidence rate per 100,000 of 9.9 for males and 5.6 for females and 9.8 for males and 7.4 for females, respectively), Northern America, Southern Europe, and Northern Europe, among others ( Sung et al, 2021 ). One possible reason, aside from females’ less exposure to PC risk factors ( Mario et al, 2018 ) including the growing rates of obesity, diabetes, and alcohol consumption, might be the sex effect on PC development and progression both in humans and rodent animal models ( Longnecker and Sumi, 1990 ; Wang et al, 2021 ). In fact, glucocorticoids and hormones have shown to affect the physiology of pancreas.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, glucocorticoids and hormones have shown to affect the physiology of pancreas. Accordingly, in the PC rat models which were treated with azaserine, estrogens could play a protective role, while androgens possibly facilitate the development of PC ( Wang et al, 2021 ). In line with that, evidence also points to the existence of an association between PC and sex hormone signaling in humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation